Spirited Conversation about Hermeneutics: A Pentecostal Hermeneut’s Response to Craig Keener’s Spirit Hermeneutics - Archer, Kenneth J. (Pneuma, 2017)
This article provides a critical assessment of Craig S. Keener’s Spirit Hermeneutics: Reading Scripture in the Light of Pentecost. It raises concerns regarding Keener’s commitment to grammatico-historical exegesis and questions whether pentecostal hermeneutics would not be better served by deconstructing the objective/subjective dichotomy that is prevalent in evangelical hermeneutics. A hermeneutical theory free from this dichotomy would coalesce nicely with postcolonial readings and with Keener’s own anecdotal testimonies of pentecostal and charismatic experiences. Lastly, the practice of principlizing the text is interrogated.